Epidermis as the "Third Brain"? - Mitsuhiro Denda (Wolters Kluwer Medknow Publications, 2015)
The role of the brain includes reception, processing, and transmission of environmental information from sensory organs to the systems of the whole body. Interestingly, the digestive organs have an independent nervous system, which has been called the "second brain". We propose that the epidermis, which forms the interface between the body and the environment, could be considered a "third brain", as it contains multiple environmental sensors and a sensory information-processing system, and it generates a variety of hormones and neurotransmitters with the potential to influence whole-body states and emotions. Specifically, epidermal keratinocytes contain sensors of mechanical stress, temperature and chemical stimuli. Furthermore, we have shown that a series of neurotransmitter receptors, which play key roles in the central nervous system and brain, are functionally expressed in keratinocytes. Cultured human keratinocytes can generate structures similar to those seen in the brain. Moreover, all the components of the hypothalamo-pituitary-adrenal (HPA) axis appear to be present in epidermal keratinocytes. Overall, these results are consistent with the hypothesis that the epidermis plays a significant role in adapting whole-body physiology, and also emotional response, to changing environments.